Construction of polydopamine-coated gold nanostars for CT imaging and enhanced photothermal therapy of tumors: an innovative theranostic strategy. Issue 23 (27th May 2016) - Li, Du; Zhang, Yongxing; Wen, Shihui; Song, Yang; Tang, Yueqin; Zhu, Xiaoyue; Shen, Mingwu; Mignani, Serge; Majoral, Jean-Pierre; Zhao, Qinghua; Shi, Xiangyang
Abstract : A theranostic nanoplatform for in vivo CT imaging and enhanced PTT of tumors is reported. Abstract : The advancement of biocompatible nanoplatforms with dual functionalities of diagnosis and therapeutics has been strongly demanded in biomedicine in recent years. In this work, we report the synthesis and characterization of polydopamine (pD)-coated gold nanostars (Au NSs) for computed tomography (CT) imaging and enhanced photothermal therapy (PTT) of tumors. Au NSs were firstly formed via a seed-mediated growth method and then stabilized with thiolated polyethyleneimine (PEI-SH), followed by deposition of pD on their surface. The formed pD-coated Au NSs (Au-PEI@pD NSs) were well characterized. We show that the Au-PEI@pD NSs are able to convert the absorbed near-infrared laser light into heat, and have strong X-ray attenuation properties. Due to the co-existence of Au NSs and pD, the light to heat conversion efficiency of the NSs can be significantly enhanced. These very interesting properties allow them to be used as a powerful theranostic nanoplatform for efficient CT imaging and enhanced phtotothermal therapy of cancer cells in vitro and the xenografted tumor model in vivo. Due to their easy functionalization nature enabled by the coated pD shell, the developed pD-coated Au NSs may be used as a versatile nanoplatform for targeted CT imaging and PTT of different types of cancers.